Examining police officer definitions of evidence-based policing: are we speaking the same language? - Telep, Cody W. (Policing and society, 2019)
Evidence-based policing has become a commonly used term in academic circles to describe policing practices guided by research evidence demonstrating their effectiveness. Little is known, however, about how police practitioners understand and define the term and the extent to which these definitions align with researcher conceptions of the term. We examine data from a survey on receptivity to research administered to 1355 police officers, supervisors, and leaders from multiple US agencies. Officers familiar with the term ‘evidence-based policing’ were asked to define it, and we coded each definition for key terms identified in the literature as relevant to evidence-based practice and for overall match to commonly used academic definitions. Our results suggest variability in both familiarity with the term ‘evidence-based policing’ and use of key terms from academic definitions based on rank. Higher ranking officers were more likely to have definitions that aligned with academic conceptions, although very few officer definitions fully matched those provided by researchers. Multivariate results suggest higher education is associated with more ‘correct’ definitions. We discuss the implications of our work for efforts to make policing more evidence-based.